Platforms mediating domestic care work as service gigs in European cities: Reorganisation of social reproduction through marketisation - Anke Strüver (Digital Geography and Society)
In European cities, lean labour platforms increasingly mediate domestic service gigs related to social reproduction, such as food delivery and cleaning tasks on-demand. This fast-growing type of platform depends on spatial proximity and the population density of cities, economic relations enabled by digital technologies and embodied gendered and racialised norms. At the same time, platforms are linked to the crisis of social reproduction and to a constant supply of people in precarious positions looking for income. The paper tackles the question how platform-mediated service gigs related to grocery shopping, cooking and cleaning change caring relationships. This comprises considerations of the dimensions of marketisation and the transformation of reproductive work symbolically, materially, and socially and is presented with a feminist perspective pointing to social reproduction as an essential but devalued part of everyday life. These endeavours are explored with findings from various case studies dealing with food delivery and cleaning platforms in Austria and Germany and are discussed with reference to relational care ethics. Put forward here is a reflection on the ways in which digital mediation of domestic care work relies on gendered and racialised norms – and how this dependence intensifies structural inequalities inherent to social reproduction.